Weaker Braking Force, A New Marker of Worse Gait Stability in Alzheimer Disease - Cheng, Qianqian; Wu, Mengxuan; Wu, Yuemin; Hu, Yaoyao; Kwapong, William Robert; Shi, Xiang; Fan, Yinying; Yu, Xin; He, Jincai; Wang, Zhen (Frontiers in Aging Neuroscience, 2020)
Background: Braking force is a gait marker associated with gait stability. This study aimed to determine the alteration of braking force and its correlation with gait stability in Alzheimer’s disease (AD). Methods: A total of 32 AD patients and 32 healthy controls (HC) were enrolled in this study. Gait parameters (braking force, gait variability and fall risk) in the walking tests of Free walk, Barrier and Count backward were measured by JiBuEn® gait analysis system. Gait variability was calculated by the coefficient of variation (COV) of stride time, stance time and swing time. Results: The Braking force of AD was significantly weaker than HC in 3 walking tests (P<0.001, P<0.001, P=0.007). Gait variability of AD showed significant elevation than HC in the walking of Count backward (COV stride: P=0.013; COV swing: P=0.006). Fall risk of AD was significantly higher than HC in 3 walking tests (P=0.001, P=0.001, P=0.001). Braking force was negatively associated with fall risks in 3 walking tests (P<0.001, P<0.001, P<0.001). There were significant negative correlations between braking force and gait variability in the walking of Free walk (COV stride: P=0.018; COV swing: P=0.013) and Barrier (COV stride: P=0.002; COV swing: P=0.001), but not Count backward (COV stride: P=0.888; COV swing: P=0.555). Conclusion: Braking force was weaker in AD compared to HC, reflecting the worse gait stability of AD. Our study suggests that weakening of braking force may be a new gait marker to indicate cognitive and motor impairment and predict fall risk in AD.